Characterizaton Of The Sandwich-Type Beam With Double Piezoelectric Materials Using Ansys Software - Jaafar, Nur Azima Aziz (Universiti Sains Malaysia, 2017)
In this study, the characteristics of the sandwich-type aluminium beam with one pair of piezoelectric patches are investigated. The study uses ANSYS-16 software as a platform to create the finite element (FE) model of the sandwich-type beam. Two case studies are investigated for beam characteristics which are the single beam and beam with piezoelectric patches. Firstly, the modal analysis has been carried out, and four natural frequencies have been determining for both cases. Then, the transient analysis is done by applying the sine wave force excitation at the edge of the right-end of the beam. The analysis is carried out for the frequency range of 0-500 Hz. The results show that, the beam is tending to excite at the natural frequencies when the excitation frequencies are closed to the natural frequencies of the beam structure. The characteristic of the piezoelectric patch as an actuator is also analyzed by applying sine wave voltage excitation to the piezoelectric patch. The results show that, the piezoelectric patch material has the possibility to be used as an actuator to reduce the vibration of the beam structure.